SIFAT ORGANOLEPTIK BURGER AYAM DENGAN METODE MEMASAK YANG BERBEDA - Lumbong, Ratnasari; Tinangon, R. M.; Rotinsulu, M. D.; Kalele, J. A. D. (Universitas Sam Ratulangi, 2017)
THE ORGANOLEPTIC CHARACTERISTIC OF CHICKEN BURGER WITH DIFFERENT COOKING METHODS. The objective of this study was to evaluate the effect of different cooking method on the characteristics of color, aroma, texture, tenderness and taste of chicken burger. Research was applied using completely randomized design with three treatments involving hedonic scale and forty replications using panelist as follows: Steaming (R1), Frying (R2), Baking (R3). Results showed that these three treatments affected significantly on color. (P<0.01), texture and tenderness (P<0.05). However, these treatments did not significantly affect on aroma and taste. Therefore, this research can be concluded that chicken burger cooked by baking method was mostly preferred by the panellist. Keywords: Chicken Burger, Steaming, Frying, Baking.